Development of Eco-friendly Low Temperature Bleaching Process for the Production of Absorbent/Bleached Cotton - RAJA, A. S. M.; ARPUTHARAJ, A.; SAXENA, SUJATA; PATIL, P. G. (Cotton Research Journal, 2021)
Raw cotton has to be treated with strong alkali and bleaching agents at elevated temperature (120Â°C) and pressure to remove the pectin, wax, nitrogenous substances and residual colour present in the fibre for the preparation of absorbent/ bleached cotton. These cotton fibres are used for medical and different industrial applications. In this study, an attempt has been made to prepare absorbent/bleached cotton at low temperature of 65Â°C using enzymes and bleach activators with prior demineralization treatment. The developed processes are compared with conventional preparatory process based on their performance properties such as absorbency, sinking time, sulphated ash, water holding capacity and whiteness. The results indicate that raw cotton could be converted into absorbent cotton by the developed low temperature processes consisting of demineralization, enzymatic and activated peroxide bleaching in a single bath. Such processed cotton fibres fulfilled the requirements as prescribed by Indian Pharmacopoeia standards. The treated fibres are subjected to FTIR and DSC analysis to know the effect of different treatments on the crystalinity and thermal behavior.